2014
DOI: 10.1007/s11910-014-0521-1
|View full text |Cite
|
Sign up to set email alerts
|

Rescue Therapy for Refractory Vasospasm after Subarachnoid Hemorrhage

Abstract: Vasospasm and delayed cerebral ischemia remain to be the common causes of increased morbidity and mortality after aneurysmal subarachnoid hemorrhage. The majority of clinical vasospasm responds to hemodynamic augmentation and direct vascular intervention; however, a percentage of patients continue to have symptoms and neurological decline. Despite suboptimal evidence, clinicians have several options in treating refractory vasospasm in aneurysmal subarachnoid hemorrhage (aSAH), including cerebral blood flow enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 96 publications
0
26
0
Order By: Relevance
“…As established vasospasm prophylaxis, CCB were investigated for their potential role in treatment 19 . Nimodipine, an L-type CCB, is currently the only pharmacologic agent showing an improvement in neurological outcomes when used for a period of 21 days, every 4 h after aneurysmal rupture, suggested by the current guidelines of the American Stroke Association 14,16 .Intravenous nicardipinedidn't show effect on outcomes after three months of use and verapamil is not selective to cerebral vasculature and its use requires more research 5,14 .…”
Section: Medical Therapy In Sah-induced Cerebral Vasospasmmentioning
confidence: 99%
See 4 more Smart Citations
“…As established vasospasm prophylaxis, CCB were investigated for their potential role in treatment 19 . Nimodipine, an L-type CCB, is currently the only pharmacologic agent showing an improvement in neurological outcomes when used for a period of 21 days, every 4 h after aneurysmal rupture, suggested by the current guidelines of the American Stroke Association 14,16 .Intravenous nicardipinedidn't show effect on outcomes after three months of use and verapamil is not selective to cerebral vasculature and its use requires more research 5,14 .…”
Section: Medical Therapy In Sah-induced Cerebral Vasospasmmentioning
confidence: 99%
“…17 Later publications showed that PTA reverses angiographic spasm of large proximal CVS, augments CBF, and may reverse neurological deficits 5,13 . Angioplasty with intraarterial (IA) administration of papaverine may show better efficacy when distal vessels are affected with CVS 9 .Some investigators have suggested that IA papaverine has influence on paradoxical vasospasm, increased intracranial pressure and has neurotoxic effects, which limited its clinical utility 9,19,22 . Several case series have shown better safety results of other IA vasodilators, including: verapamil, nicardipine, nimodipine, and milrinone, than papaverine, but that was not supported by adequate trials 5,17 .Several retrospective studies with propose neurological progress after one dose of IA verapamil…”
Section: Interventional Treatmentmentioning
confidence: 99%
See 3 more Smart Citations